IoT-Based UPS Device Electricity Usage Monitoring System with MQTT Protocol - Adit Oktopryadin; Adi Purnama (Politeknik Negeri Batam, 2025)
The continuity of network device operations heavily relies on stable power supply, especially in digital environments that demand uninterrupted connectivity. One commonly used solution to ensure power continuity is the Uninterruptible Power Supply (UPS). However, traditional UPS systems often lack real-time monitoring mechanisms, leaving users uninformed during the transition from main electricity to UPS power. To address this challenge, this study proposes the design of a UPS power consumption monitoring system based on the Internet of Things (IoT) using the Message Queuing Telemetry Transport (MQTT) communication protocol. The system integrates a PZEM-004T power sensor and ESP32 microcontroller to read electrical parameters such as voltage, current, and power in real-time, and displays the data through a digital dashboard built with Node-RED. The implementation results show that the system can automatically detect changes in power source status and record electrical parameters with an average error rate below 1%, both during normal grid operation and when switching to UPS power. This system is expected to serve as a practical and efficient solution for minimizing network downtime caused by power disruptions.